Nurse academicians’ experiences in the pandemic and their perspectives on future pandemics – a qualitative study - İnce, Sevecen Çelik and Dinçer, Yeliz (European Journal of Clinical and Experimental Medicine, 2023)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. The COVID-19 pandemic, which affects the whole world, has also significantly affected nurses, nursing students and nursing academicians. This study aims to determine the experiences of nurse academicians and their perspectives on possible future pandemics. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. The study is a descriptive qualitative type. It was conducted in September-December 2022 in the Department of Nursing, Faculty of Health Sciences, of a university located in the west of Turkey. The sample of the study consisted of 11 nurse academicians. Personal Information Form, Interview Form on COVID-19 Pandemic Experiences and voice recorder were used to collect data. Data analysis was done with content analysis. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. As a result of the analysis of the data obtained from the interviews, four main themes emerged: (1) nurse academicians and nursing education in the pandemic, (2) the impact of the pandemic on life, (3) the gains in the pandemic, and (4) suggestions for future pandemics. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. As a result of this study, it was determined that nurse academicians’ families, social, and academic lives, and health were deeply affected during the pandemic, but they also found opportunities during the pandemic. It is thought that guidelines and action plans are needed to ensure the safety of nursing education for future pandemic-like situations and to minimize the problems experienced by academic nurses. For this, it is recommended to reconsider the technical possibilities and methods of education.